Degradation evaluation of Si3N4 ceramic surface layer in contact with molten Al using microcantilever beam specimens. Issue 14 (November 2017) - Fujita, Saho; Tatami, Junichi; Yahagi, Tsukaho; Takahashi, Takuma; Iijima, Motoyuki
Abstract: Although Si3 N4 ceramics are often utilized as structural components in the Al casting industry due to their excellent properties, they occasionally suffer breakage after long-term use. In this study, the bending strength, fracture toughness, and Young's modulus in the vicinity of the Si3 N4 ceramic surfaces after contact with molten Al were evaluated using microcantilever beam specimens, which were fabricated using a focused ion beam technique. Fracture testing of the specimens was carried out by nanoindentation. The bending strength of the ceramic surface before and after contact with molten Al was 5.89 ± 1.33 and 3.03 ± 0.28 GPa, respectively. The fracture toughness of the corroded layer in Si3 N4 ceramics also decreased compared to that of the polished surface. Using fractography by observation with scanning electron microscopy, it was shown that changes in the grain boundary glassy phase resulted in the degradation of strength and fracture toughness.